Parasitism and host dispersal plasticity in an aquatic model system. (3rd July 2021) - Zilio, Giacomo; Nørgaard, Louise S.; Petrucci, Giovanni; Zeballos, Nathalie; Gougat‐Barbera, Claire; Fronhofer, Emanuel A.; Kaltz, Oliver
Abstract: Dispersal is a central determinant of spatial dynamics in communities and ecosystems, and various ecological factors can shape the evolution of constitutive and plastic dispersal behaviours. One important driver of dispersal plasticity is the biotic environment. Parasites, for example, influence the internal condition of infected hosts and define external patch quality. Thus, state‐dependent dispersal may be determined by infection status and context‐dependent dispersal by the abundance of infected hosts in the population. A prerequisite for such dispersal plasticity to evolve is a genetic basis on which natural selection can act. Using interconnected microcosms, we investigated dispersal in experimental populations of the freshwater protist Paramecium caudatum in response to the bacterial parasite Holospora undulata . For a collection of 20 natural host strains, we found substantial variation in constitutive dispersal and to a lesser degree in dispersal plasticity. First, infection tended to increase or decrease dispersal relative to uninfected controls, depending on strain identity, indicative of state‐dependent dispersal plasticity. Infection additionally decreased host swimming speed compared to the uninfected counterparts. Second, for certain strains, there was a weak negative association between dispersal and infection prevalence, such that uninfected hosts dispersed less when infection was more frequent in the population, indicating context‐dependent dispersal plasticity. Future experiments may test whether the observed differences in dispersal plasticity are sufficiently strong to be picked up by natural selection. The evolution of dispersal plasticity as a strategy to mitigate parasite effects spatially may have important implications for epidemiological dynamics. Abstract : Dispersal plasticity may be advantageous in mitigating adverse interactions with parasites and may have important implications for epidemiological dynamics. Here we examined state‐ and context‐dependent dispersal plasticity in an aquatic model system. Parasite infection affected dispersal depending on the host strain identity (state‐dependent dispersal), and uninfected hosts tended to disperse less at higher infection prevalence (context‐dependent dispersal).